Alteration of serum amino acid profiles by dietary adenine supplementation inhibits fatty liver development in rats - Hiroki Nishi (Nature Portfolio, 2020)
Abstract Studies on animal models have demonstrated that feeding a low-arginine diet inhibits triacylglycerol (TAG) secretion from the liver, resulting in marked fatty liver development in rats. Here, we first showed that culturing hepatocytes in the medium mimicking the serum amino acid profile of low-arginine diet-fed rats induced TAG accumulation in the cells, indicating that the specific amino acid profile caused TAG accumulation in hepatocytes. Dietary adenine supplementation completely recovered hepatic TAG secretion and abolished hepatic TAG accumulation in rats. A comprehensive non-linear analysis revealed that inhibition of hepatic TAG accumulation by dietary adenine supplementation could be predicted using only serum amino acid concentration data. Comparison of serum amino acid concentrations indicated that histidine, methionine, and branched-chain amino acid (BCAA) concentrations were altered by adenine supplementation. Furthermore, when the serum amino acid profiles of low-arginine diet-fed rats were altered by modifying methionine or BCAA concentrations in their diets, their hepatic TAG accumulation was abolished. Altogether, these results suggest that an increase in methionine and BCAA levels in the serum in response to dietary arginine deficiency is a key causative factor for hepatic TAG accumulation, and dietary adenine supplementation could disrupt this phenomenon by altering serum amino acid profiles.